2015
DOI: 10.1002/ajmg.a.36903
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea in young infants with Down Syndrome evaluated in a Down Syndrome specialty clinic

Abstract: Introduction Children with Down syndrome (DS) experience congenital and functional medical issues that predispose them to obstructive sleep apnea (OSA). Research utilizing stringent age criteria among samples of infants with DS and OSA is limited. This study examines clinical correlates of OSA among infants with DS. Materials and Methods A retrospective chart review was conducted of infants ≤6 months of age referred to a DS clinic at a tertiary children’s hospital over five-years (n=177). Chi-square tests an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
18

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 36 publications
4
59
0
18
Order By: Relevance
“…Finally, nine studies with 629 individuals were found using an AHI cutoff ≥ 2.0, indicating an OSA prevalence of 74.2% (95% CI: 65.1 to 82.4) [3], [6], [59], [62], [65], [68], [70], [72], [77]. Thus, as would be expected, OSA prevalence decreases somewhat as more restrictive AHI cutoffs are utilized.…”
Section: Prevalence Of Osa and Potential Moderatorsmentioning
confidence: 93%
See 2 more Smart Citations
“…Finally, nine studies with 629 individuals were found using an AHI cutoff ≥ 2.0, indicating an OSA prevalence of 74.2% (95% CI: 65.1 to 82.4) [3], [6], [59], [62], [65], [68], [70], [72], [77]. Thus, as would be expected, OSA prevalence decreases somewhat as more restrictive AHI cutoffs are utilized.…”
Section: Prevalence Of Osa and Potential Moderatorsmentioning
confidence: 93%
“…A cutoff AHI of ˂ 2/hr was utilized in most of these studies to define the absence of OSA, while 2.0-4.9/hr is often used to define mild OSA, 5.0-9.9 to define moderate OSA, and ˃10/hr to define severe OSA. Descriptively, across these child studies 21.5% of children had mild OSA (95% CI: 16.7 to 26.7), 20.3% moderate OSA (17.3 to 23.5), and 30.4% had severe OSA (20.5 to 41.2) [3], [6], [59], [62], [63], [65], [66], [68], [70], [76], [77]. All but two of these 11 child studies used an AHI cutoff of 2/hr for diagnosing OSA [11], [76].…”
Section: Prevalence Of Osa and Potential Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,13 . Bu durum DS'li çocuklarda; sağlıklı çocuklara oranla çok daha yüksek oranlarda OUAS'a rastlandığını göstermektedir.…”
Section: Tartiġma Ouas Ve Ds (Tablo 2)unclassified
“…However, Menon and Kumar (2013) found a supine sleeping posture is more commonly associated with obstructive sleep apnea (OSA), a common condition in infants, particularly those born prematurely. Katz, Mitchell, and D'Ambrosia (2012) indicate infants have Bboth anatomical and physiological predispositions toward airway obstruction and gas exchange abnormalities including superiorly placed larynx, increased chest wall compliance, ventilation-perfusion mismatching, and ventilatory control instability.^In addition to prematurity, OSA is increasingly common in infants born with Down syndrome (Goffinski et al, 2015), craniofacial conditions, and various other genetic syndromes (Bacher et al, 2011). Infants with OSA who sleep in supine positions have been found to suffer decreased sleep quality and efficiency such as frequently interrupted sleep due to a significant increase in the number of awakenings and obstructions (Bhat et al, 2006).…”
mentioning
confidence: 99%